Resin composition, molded product obtained by molding the same, and method for producing resin composition

The resin composition, featuring a crystalline polymer and organic solvent, addresses the challenge of maintaining shape and reducing molding temperature, achieving enhanced mechanical properties and energy efficiency.

JP7673643B2Active Publication Date: 2025-05-09ZEON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021567376
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-25
Filing Date
2020-12-17
Publication Date
2025-05-09
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

Conventional resin materials struggle to achieve both improved shape maintenance of molded products and a lower heating temperature required in the molding process.

Method used

A resin composition comprising a crystalline polymer with structural units derived from a cyclic olefin compound and an organic solvent, with a density of 1.02 g/cm³ and an organic solvent content between 0.1% to 10% by mass, which enhances shape retention and reduces molding temperature.

Benefits of technology

The resin composition exhibits high shape retention and requires a lower heating temperature during molding, improving both the mechanical properties and energy efficiency of the molding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007673643000001
    Figure 0007673643000001
Patent Text Reader

Abstract

A resin composition which contains: a crystalline polymer that has a structural unit derived from a cyclic olefin compound; and an organic solvent. This resin composition has a density of 1.02 g / cm3 or more; and the content ratio of the organic solvent relative to 100% by mass of the polymer is from 0.1% by mass to 10% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a molded product obtained by molding the resin composition, and a method for producing the resin composition. [Background technology]

[0002] Conventionally, various methods for obtaining a resin film having excellent properties have been studied. For example, Patent Document 1 proposes producing a resin film having excellent dimensional stability when heated by stretching a resin film mainly composed of a crystalline alicyclic structure-containing resin, and contacting the stretched film obtained with a hydrocarbon solvent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-26909 A Summary of the Invention [Problem to be solved by the invention]

[0004] When molding a resin into a desired shape, it is common to carry out a molding process under heating conditions. Here, a lower heating temperature in the molding process is advantageous in that the time required for heating and cooling the molded object is shorter than that in the case of a higher heating temperature, and therefore the molding cycle, which is the time required for one molding, can be shortened and energy consumption is low. In addition, it is required that the molded product obtained by molding the resin into a desired shape does not lose its shape, that is, has excellent shape retention. However, with conventional resin materials, it was difficult to simultaneously improve the shape retention of the obtained molded product and reduce the heating temperature required in the molding process. Therefore, the present invention aims to provide a resin composition and a manufacturing method thereof that have high shape retention when a molded product is formed and that require a reduced heating temperature in the molding process. Furthermore, the present invention aims to provide a molded product with high shape retention. [Means for solving the problem]

[0005] The present inventors have conducted intensive research with the aim of solving the above problems. The present inventors have found that a high-density resin composition can be created by incorporating an organic solvent at a predetermined ratio into a crystalline polymer having a structural unit derived from a cyclic olefin compound. Furthermore, the present inventors have newly found that such a resin composition has the properties of high shape retention when a molded product is formed, and low heating temperature required in the molding process.

[0006] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the resin composition of the present invention comprises a crystalline polymer having a structural unit derived from a cyclic olefin compound and an organic solvent, and has a density of 1.02 g / cm 3 The resin composition is characterized in that the content of the organic solvent is 0.1% by mass or more and 10% by mass or less relative to 100% by mass of the polymer. Such a resin composition has high shape retention when a molded product is formed, and requires a low heating temperature in the molding process. In this specification, a polymer being "crystalline" means that the melting point can be observed by differential scanning calorimetry (DSC) by optimizing the measurement conditions, etc., and is a property determined by the stereoregularity of the polymer chain. The content of the organic solvent in the resin composition can be measured by the method described in the Examples of this specification.

[0007] In the resin composition of the present invention, the polymer is preferably a hydrogenated polymer. A resin composition containing a hydrogenated polymer can provide a molded product having excellent heat resistance.

[0008] In the resin composition of the present invention, the hydrogenation rate of the polymer is preferably 90% or more. A resin composition containing a polymer having a hydrogenation rate of 90% or more can provide a molded product having even more excellent heat resistance. The "hydrogenation rate" of a polymer means the ratio of carbon-carbon double bonds contained in the main chain and side chain of the polymer as a precursor to be subjected to the hydrogenation treatment that are hydrogenated in the hydrogenation treatment. The "hydrogenation rate" of a polymer can be measured according to the method described in the Examples of this specification.

[0009] Furthermore, in the resin composition of the present invention, the organic solvent is preferably a non-polar solvent. If the organic solvent included in the resin composition is a non-polar solvent, the shape retention when a molded product is formed using the resin composition can be further improved.

[0010] The present invention also aims to advantageously solve the above problems, and the molded article of the present invention is formed by molding any one of the above-mentioned resin compositions. By using any one of the above-mentioned resin compositions, a molded article having high shape retention can be obtained.

[0011] The present invention also aims to advantageously solve the above-mentioned problems, and a method for producing a resin composition of the present invention includes the steps of: immersing a polymer material made of a crystalline polymer having a structural unit derived from a cyclic olefin compound in an organic solvent; drying the polymer material that has been subjected to the immersion step under an atmosphere with a pressure of 1000 Pa to 6000 Pa and a temperature of 5° C. to 35° C. to obtain a resin composition having a density of 1.02 g / cm or less; 3 The present invention is characterized in that the method includes a drying step of obtaining a resin composition having the above-mentioned properties and a content of the organic solvent in a range of 0.1% by mass to 10% by mass of the polymer. According to this production method, the resin composition of the present invention can be efficiently produced. In this specification, "pressure" means gauge pressure. Effect of the Invention

[0012] According to the present invention, it is possible to provide a resin composition that has high shape retention when a molded product is formed and requires a reduced heating temperature in the molding step, and a method for producing the same. Furthermore, according to the present invention, a molded product having high shape retention can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail. The resin composition of the present invention can be used in various fields as a resin material for constituting various molded articles. Moreover, the resin composition of the present invention can be efficiently produced according to the method for producing the resin composition of the present invention.

[0014] (Resin composition) The resin composition of the present invention includes a crystalline polymer having a structural unit derived from a cyclic olefin compound and an organic solvent. The resin composition of the present invention has a density of 1.02 g / cm 3 The resin composition of the present invention is characterized in that the content of the organic solvent is 0.1% by mass or more and 10% by mass or less relative to 100% by mass of the polymer. The resin composition of the present invention has high shape retention when formed into a molded product, and requires a low heating temperature in the molding process.

[0015] <Polymer> The polymer contained in the resin composition of the present invention is a crystalline polymer having a structural unit derived from a cyclic olefin compound. Such a polymer may be a polymer containing only a structural unit derived from a cyclic olefin compound as a repeating unit, or may contain other units other than the structural unit derived from a cyclic olefin compound. Such other units are not particularly limited, and any unit may be mentioned as long as they are copolymerizable with the structural unit derived from a cyclic olefin compound.

[0016] <<Structural units derived from cyclic olefin compounds>> The structural unit derived from a cyclic olefin compound is a structural unit derived from a cyclic olefin compound contained in a polymer obtained by carrying out a polymerization reaction using a cyclic olefin compound as a monomer. The cyclic olefin compound is a compound having a ring structure formed by carbon atoms and having a carbon-carbon double bond in the ring structure. Specifically, the cyclic olefin compound includes norbornene-based monomers and the like.

[0017] The norbornene-based monomer is a monomer that contains a norbornene ring. Norbornene monomers include bicyclic monomers such as bicyclo[2.2.1]hept-2-ene (common name: norbornene), 5-ethylidene-bicyclo[2.2.1]hept-2-ene (common name: ethylidenenorbornene) and their derivatives (those having a substituent on the ring); Tricyclo[4.3.0 1,6 .1 2,5 ] Deca-3,7-diene (common name: dicyclopentadiene) and its derivatives, and other tricyclic monomers; 7,8-Benzotricyclo[4.3.0.1 2,5 ]dec-3-ene (common name: methanotetrahydrofluorene, also known as 1,4-methano-1,4,4a,9a-tetrahydrofluorene) and its derivatives, tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene (common name: tetracyclododecene), 8-ethylidenetetracyclo[4.4.0.1 2,5 .1 7,10 4-cyclic monomers such as 4-(2-phenylene)-3-dodecene and derivatives thereof;

[0018] Examples of the substituents on these monomers include alkyl groups such as methyl and ethyl groups; alkenyl groups such as vinyl groups; alkylidene groups such as propan-2-ylidene; aryl groups such as phenyl groups; hydroxy groups; acid anhydride groups; carboxyl groups; and alkoxycarbonyl groups such as methoxycarbonyl groups.

[0019] When all repeating units contained in the polymer are taken as 100% by mass, the proportion of structural units derived from a cyclic olefin compound can be appropriately selected depending on the intended use of the resin composition, but is usually 30% by mass or more, preferably 50% by mass or more, more preferably 70% by mass or more, and may be 100% by mass.

[0020] <<Polymer hydrogenation rate>> The polymer is preferably a hydrogenated product. From the viewpoint of improving the heat resistance of the resin composition, the hydrogenation rate of the polymer is preferably 98.0% or more, and more preferably 99.0% or more.

[0021] <<Polymer melting point>> From the viewpoint of heat resistance of the resin composition, the melting point of the polymer is preferably 110°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher. The upper limit of the melting point of the polymer is not particularly limited, but from the viewpoint of moldability, it is preferably 400°C or lower. The melting point of the polymer can be adjusted by changing the method for producing the polymer. For example, it can be adjusted by changing the type and / or amount of the polymerization catalyst and molecular weight modifier used when preparing the polymer. The "melting point" of a polymer can be measured by a differential scanning calorimeter, for example, by using the method described in the examples of this specification.

[0022] <<Weight average molecular weight of polymer>> The weight average molecular weight of the polymer can be appropriately selected according to the application.For example, the weight average molecular weight of the polymer is preferably 10,000 or more, more preferably 15,000 or more, even more preferably 20,000 or more, particularly preferably 25,000 or more, preferably 1,000,000 or less, more preferably 500,000 or less, even more preferably 300,000 or less, even more preferably 200,000 or less, and particularly preferably 150,000 or less.If the weight average molecular weight is 10,000 or more, the mechanical strength of the resin composition can be increased, and if the weight average molecular weight is 1,000,000 or less, the processability of the resin composition can be increased. The weight-average molecular weight of the polymer can be adjusted by changing the production method, for example, by changing the type and / or amount of a polymerization catalyst and a molecular weight regulator when preparing the polymer.

[0023] <<Polymer stereoregularity>> The degree of syndiotactic stereoregularity (ratio of racemo-dyads) in the stereostructure of the polymer is not particularly limited as long as the polymer is crystalline, and can be appropriately selected according to the application of the resin composition. For example, the ratio of racemo-dyads in the polymer can be 0% or more and 35% or less, or 65% or more and 100% or less. The "ratio of racemo-dyads in the polymer" can be measured according to the method described in the examples of this specification.

[0024] <<Polymer isomerization rate>> Depending on the structural units derived from the cyclic olefin compound constituting the polymer, cis-type structural units (I) and trans-type structural units (II) may be mixed in the polymer. In this case, the ratio (isomerization rate) of the trans-type structural units (II) to the total of the cis-type structural units (I) and the trans-type structural units (II) in the polymer is preferably 20% or less, more preferably 15% or less. The isomerization rate of the polymer can be adjusted by changing the production method. Specifically, the isomerization rate of the polymer can be adjusted by changing the type and / or amount of the hydrogenation catalyst used when subjecting the polymer to hydrogenation treatment.

[0025] <<Polymer Preparation Method>> The polymer can be synthesized according to a known method without any particular limitation. For example, the polymer can be prepared by polymerizing a monomer composition containing a cyclic olefin compound and any additives, etc., using a known ring-opening polymerization catalyst and a known organometallic reducing agent that can be optionally used in combination with such a catalyst (see, for example, JP 2016-26909 A). The polymerization reaction can usually be carried out in an organic solvent. Examples of such organic solvents include, but are not limited to, aliphatic hydrocarbons such as pentane, hexane, and heptane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, ethylcyclohexane, diethylcyclohexane, decahydronaphthalene, bicycloheptane, tricyclodecane, hexahydroindene, and cyclooctane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated aliphatic hydrocarbons such as dichloromethane, chloroform, and 1,2-dichloroethane; halogenated aromatic hydrocarbons such as chlorobenzene and dichlorobenzene; nitrogen-containing hydrocarbons such as nitromethane, nitrobenzene, and acetonitrile; ethers such as diethyl ether and tetrahydrofuran; and mixed solvents of combinations of these. Other additives and polymerization conditions may also be appropriately changed as necessary (see, for example, JP 2016-26909 A).

[0026] <<Method of Hydrogenating Polymers>> The polymer can be made into a hydrogenated product by (a) adding a hydrogenating agent to the polymer obtained by polymerizing a cyclic olefin compound, followed by heating and reacting (hydrogen transfer hydrogenation reaction); or (b) adding a hydrogenation catalyst, followed by adding hydrogen and reacting (catalytic hydrogenation reaction). Note that the stereoregularity of the polymer is usually unchanged before and after the hydrogenation treatment.

[0027] The hydrogenation agent used in the above-mentioned (a) hydrogen transfer hydrogenation reaction is not particularly limited, and any hydrogenation agent can be used as long as it is capable of hydrogenating the carbon-carbon double bonds present in the polymer. Examples of the hydrogenation agent include hydrazine and paratoluenesulfonylhydrazide. In addition, as the hydrogenation catalyst used in the above-mentioned (b) catalytic hydrogenation reaction, a homogeneous catalyst or a heterogeneous catalyst known as a hydrogenation catalyst for olefin compounds can be used (for example, see JP 2016-26909 A).

[0028] When a hydrogenated product is used as the polymer to be blended in the resin composition of the present invention, it is preferable to carry out a drying step of drying the obtained hydrogenated product / polymer (unhydrogenated) after the hydrogenation treatment of the polymer, or after the polymerization step when the synthesized polymer is used without hydrogenation. The conditions of the drying step are not particularly limited as long as the organic solvent used as the polymerization solvent and the hydrogenation solvent can be removed from the object to be dried. For example, the drying step can be appropriately carried out at a temperature of more than 35°C, in an atmosphere with a pressure of 1 Pa to 100 Pa, and for a drying time of 10 hours to 48 hours.

[0029] <Organic solvent> The resin composition of the present invention contains an organic solvent. The organic solvent is not particularly limited, and a polar solvent such as an alcohol, and a non-polar solvent can be used. Among them, a non-polar solvent can be preferably used. Examples of the non-polar solvent include toluene, xylene, cyclohexane, chloroform, carbon disulfide, benzene, mesitylene, hexane, pentane, chlorobenzene, and anisole. Among them, toluene, xylene, cyclohexane, chloroform, and carbon disulfide are preferable as the non-polar solvent. These can be used alone or in combination.

[0030] <<Organic solvent content>> The content of the organic solvent in the resin composition must be 0.1% by mass or more and 10% by mass or less, based on 100% by mass of the polymer. Furthermore, the content of the organic solvent is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, based on 100% by mass of the polymer. If the content of the organic solvent in the resin composition is equal to or more than the lower limit, it is possible to satisfactorily increase the density of the resin composition and reduce the heating temperature required in the molding process. If the content of the organic solvent in the resin composition is equal to or less than the upper limit, it is possible to improve the shape retention when a molded product is formed. The content of the organic solvent can be adjusted according to the method described in detail in the section (Method for producing a resin composition).

[0031] <Other ingredients> Depending on the intended use, the resin composition may contain additives such as antioxidants, crystal nucleating agents, fillers, flame retardants, flame retardant assistants, colorants, antistatic agents, ultraviolet absorbers, light stabilizers, near infrared absorbers, and lubricants. The content of these can be appropriately determined depending on the intended use, but is preferably 50% by mass or less, and more preferably 30% by mass or less, based on 100% by mass of the polymer.

[0032] Some common cyclic olefin resins contain a plasticizer as an additive. Conventionally, plasticizers have been added for the purpose of softening the resin and improving moldability. However, the resin composition of the present invention preferably does not contain a plasticizer. By not containing a plasticizer in the resin composition, it is possible to suppress the occurrence of disadvantages caused by the plasticizer, such as bleed-out during resin molding, in a molded product formed using the resin composition.

[0033] <Density of Resin Composition> The density of the resin composition of the present invention is 1.02 g / cm 3 Must be at least 1.12g / cm 3 When the density of the polymer is equal to or higher than the lower limit, the shape retention of a molded product can be improved. When the density of the polymer is equal to or lower than the upper limit, the moldability of the resin composition can be improved.

[0034] (Method of producing resin composition) The method for producing a resin composition of the present invention includes a step of immersing a polymer material made of a crystalline polymer having a structural unit derived from a cyclic olefin compound in an organic solvent, and drying the polymer material that has been subjected to the immersion step under an atmosphere of a pressure of 1000 Pa to 6000 Pa and a temperature of 5° C. to 35° C. to obtain a resin composition having a density of 1.02 g / cm. 3 The method is characterized by including a drying step of obtaining a resin composition having the above-mentioned properties and an organic solvent content of 0.1% by mass or more and 10% by mass or less relative to 100% by mass of the polymer.

[0035] <Soaking process> In the immersion step, the polymer material consisting of the above-mentioned "crystalline polymer having structural units derived from a cyclic olefin compound" is immersed in an organic solvent. As the organic solvent, the above-mentioned non-polar solvent can be suitably used. The shape of the polymer material subjected to this step can be any shape such as pellets, small pieces, powder, etc. Here, "small pieces" means a plate shape cut into any uniform size.

[0036] Among them, from the viewpoint of obtaining a resin composition having excellent production efficiency and uniform organic solvent content, it is preferable to use pellets and small pieces of moderate size as the immersion object. If the size of the immersion object is excessively small or powdery, the obtained resin composition may have poor moldability. On the other hand, if the size of the immersion object is excessively large, it becomes necessary to extend the immersion time, which may result in poor production efficiency. When the immersion object is in the form of a pellet, for example, a pellet having a pellet diameter of 0.2 mm to 2.5 mm and a pellet length of 0.5 mm to 5 mm can be suitably used. When the immersion object is in the form of a small piece, more specifically, when it is rectangular in plan view, for example, a pellet having a side length of 0.5 mm to 5 mm and a thickness of 0.2 mm to 2.5 mm can be suitably used. In addition, the ratio between the pellet diameter and the pellet length (pellet length / pellet diameter) and the ratio between the thickness and the length of one side (length of one side / thickness) can each be more than 1 time and not more than 25 times. According to the methods described above in the sections <<Method of Preparing Polymer>> and <<Method of Hydrogenating Polymer>>, a powdered polymer (unhydrogenated) / hydrogenated product is usually obtained. Any molding method can be used to mold such a polymer (unhydrogenated) / hydrogenated product into any shape such as pellets or small pieces. When a molding method involving heating is performed, the heating temperature can be, for example, in the range of (melting point + 10)°C or more and (melting point + 100)°C or less of the object to be molded in the molding method (i.e., polymer (unhydrogenated) or hydrogenated product).

[0037] The immersion time in the immersion step may be, for example, from 10 minutes to 48 hours. The immersion temperature in the immersion step may be, for example, from 5° C. to 35° C. These conditions in the immersion step may be appropriately adjusted in consideration of the size of the object to be immersed, the affinity between the organic solvent used for immersion and the composition of the polymer, and the like, so that the desired density and content of the organic solvent are satisfied.

[0038] <Drying process> In the drying step, the polymer material that has been subjected to the immersion step is dried under predetermined temperature and pressure conditions to obtain a resin composition having a density and an organic solvent content within a predetermined range. The temperature condition in the drying step must be 5°C or higher and 35°C or lower, and preferably 10°C or higher and 30°C or lower. The pressure condition of the atmosphere in the drying step must be 1000 Pa or higher and 6000 Pa or lower in terms of gauge pressure. Furthermore, the drying time in the drying step is preferably 3 minutes or longer and shorter than 30 minutes. The ranges of the density and organic solvent content of the resin composition obtained through the drying step are as described above. In addition, in the drying step, prior to exposing the polymer material to a drying atmosphere satisfying the above-mentioned temperature and pressure conditions, it is preferable to remove the organic solvent remaining on the surface of the polymer material immediately after the immersion step by, for example, wiping the surface of the polymer material that has been subjected to the immersion step.

[0039] (molded product) The molded article of the present invention is formed using the above-mentioned resin composition of the present invention. Since the molded article of the present invention is formed by molding the resin composition of the present invention, the molded article of the present invention has excellent shape retention.

[0040] The method for producing the molded product is not particularly limited. The resin composition can be molded into a molded product of a desired shape by using a known molding method such as injection molding, compression molding, extrusion molding, etc. The shape of the molded product can be appropriately selected depending on the application.

[0041] The uses of the molded product of the present invention are not particularly limited, but include, for example: Optical materials such as optical disks, optical lenses, prisms, light diffusion plates, optical cards, optical fibers, optical mirrors, liquid crystal display element substrates, light guide plates, polarizing films, and retardation films; Containers for liquid, powder, or solid medicines (liquid medicine containers for injection, ampoules, vials, prefilled syringes, infusion bags, inner layers, middle layers, outer layers of multilayer films, sealant films, sealed medicine bags, press-through packages, solid medicine containers, eye drop containers, etc.), sampling containers (sampling test tubes for blood tests, medicine container caps, blood collection tubes, specimen containers, etc.), medical instruments (syringes, etc.), sterilized containers for medical instruments (scalpels, forceps, gauze, contact lenses, etc.), laboratory and analytical instruments (beakers, petri dishes, flasks, test tubes, centrifuge tubes, etc.), medical optical parts (plastic lenses for medical tests, etc.), piping materials (medical infusion tubes, piping, joints, valves, etc.), artificial organs and their parts (tooth bases, artificial hearts, artificial tooth roots, etc.), and other medical equipment; Food containers such as bottles, returnable bottles, baby bottles, films, shrink films, etc.; Equipment for processing electronic components, such as processing or transport containers (tanks, trays, carriers, cases, etc.), protective materials (carrier tapes, separation films, etc.), piping (pipes, tubes, valves, flow meters, filters, pumps, etc.), containers for liquids (sampling containers, bottles, ampoule bags, etc.); Electrical insulating materials such as coating materials (for electric wires, cables, etc.), housings for consumer and industrial electronic devices (copying machines, computers, printers, televisions, video decks, video cameras, etc.), structural members (parabolic antenna structural members, flat antenna structural members, radar dome structural members, etc.); Circuit boards such as general circuit boards (rigid printed circuit boards, flexible printed circuit boards, multilayer printed wiring boards, etc.), high-frequency circuit boards (circuit boards for satellite communication equipment, etc.); base materials for transparent conductive films (liquid crystal substrates, optical memory, surface heating elements, etc.); Semiconductor encapsulation materials (transistor encapsulation materials, IC encapsulation materials, LSI encapsulation materials, LED encapsulation materials, etc.), encapsulation materials for electric and electronic components (motor encapsulation materials, capacitor encapsulation materials, switch encapsulation materials, sensor encapsulation materials, etc.); These include automotive interior materials such as room mirrors and meter covers; and automotive exterior materials such as door mirrors, fender mirrors, beam lenses, and light covers. EXAMPLES

[0042] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In the following description, the "%" and "parts" that represent amounts are based on mass unless otherwise specified. In addition, the pressures shown in the following description are gauge pressures, and the pressures referred to as "vacuum" are 1 Pa or more and 100 Pa or less, the pressures referred to as "reduced pressure" are 1000 Pa or more and 6000 Pa or less, and the pressures referred to as "normal pressure" are 900 hPa or more and 1100 hPa or less. In the examples and comparative examples, the products obtained were measured, analyzed and evaluated according to the following methods.

[0043] <Weight average molecular weight of hydrogenated ring-opened polymer> The weight-average molecular weight of the hydrogenated polymer obtained by ring-opening polymerization of norbornene monomers in Production Examples 1 to 5 (hereinafter also referred to as "hydrogenated ring-opened polymer") was measured as a standard polystyrene equivalent value by gel permeation chromatography (GPC) using 1,2,4-trichlorobenzene as an eluent. The measurement device used was HLC8121GPC / HT (manufactured by Tosoh Corporation). The sample was prepared by heating and dissolving the hydrogenated ring-opened polymer in 1,2,4-trichlorobenzene at 140°C to a sample concentration of 1 mg / ml. The measurements were performed using three TSKgel GMHHR·H(20)HT (Tosoh Corporation) columns connected in series under conditions of a flow rate of 1.0 ml / min, sample injection volume of 300 μl, and column temperature of 140°C. <Stereoregularity> The stereoregularities of the hydrogenated ring-opened polymers obtained in Production Examples 1 to 5 are as follows: 13Specifically, the ring-opening polymer hydrogenated product was measured by the inverse-gated decoupling method using chloroform-d (when norbornene was used as the cyclic olefin compound) or a mixed solvent of 1,3,5-trichlorobenzene-d3 / orthodichlorobenzene-d4 (volume ratio: 2 / 1; when dicyclopentadiene or tetracyclododecene was used as the cyclic olefin compound) at 60°C (when the solvent was chloroform-d) or 200°C (when the solvent was the above mixed solvent). 13 C-NMR measurements were performed. The ratio (%) of the signal intensity originating from the racemo dyad to the total signal intensity originating from the meso dyad and the racemo dyad was calculated using the peak at 77.0 ppm in chloroform-d or the peak at 127.5 ppm in ortho-dichlorobenzene-d as the reference shift, and the proportion of the racemo dyad was calculated. <Hydrogenation rate> The ring-opening polymers before hydrogenation and the hydrogenated ring-opening polymers obtained in Production Examples 1 to 5 were 1 H-NMR measurement was carried out to determine the percentage (%) of hydrogenated carbon-carbon double bonds contained in the main chain and side chains of the polymer. <Melting point and glass transition point> The melting point was measured by increasing the temperature at a rate of 10°C / min using a differential scanning calorimeter (DSC; X-DSC7000, manufactured by SII Nano Technology Co., Ltd.), and the temperature point at which the endothermic heat was greatest at the peak of the first-order phase transition of crystal melting was taken as the melting point. The glass transition point was measured by melting the resin composition at a high temperature, then instantly immersing it in liquid nitrogen in the molten state and rapidly cooling it to obtain an amorphous sample, and then increasing the temperature at a rate of 10°C / min using a differential scanning calorimeter (DSC). --Measurement of pre-molding and post-molding melting points-- "Melting point before molding": The melting points of the resin compositions A to H obtained in Examples 1 to 8, and the hydrogenated ring-opening polymers a to d, and h obtained in Comparative Examples 1 to 5 were measured as described above, and are shown in Table 1 as "melting points before molding". "Melting point after molding": The molten material obtained when measuring the "melting point before molding" was cooled and recrystallized to prepare a test sample, and its melting point was measured again in the same manner as above. The obtained value was referred to as the "melting point after molding" and is shown in Table 1. <Isomerization rate> The isomerization rate of the hydrogenated ring-opening polymer is 13 The isomerization rate was calculated by C-NMR measurement (solvent: deuterated chloroform, measurement temperature: 60° C.). Specifically, in the obtained NMR spectrum, the signal intensity of the trans-type structural unit (II) was divided by the sum of the signal intensity of the cis-type structural unit (I) and the signal intensity of the trans-type structural unit (II), and the result was multiplied by 100 to calculate the isomerization rate (percentage). <Organic solvent content> In measuring the organic solvent content (based on the amount of hydrogenated ring-opening polymer) of the resin compositions A to H and the hydrogenated ring-opening polymers a to d and h obtained in the examples and comparative examples, the measurement samples were dried for 7 days under conditions of 100°C and 100 Pa. Then, the organic solvent content of the measurement sample before drying was obtained from the change in mass of the measurement sample before and after drying.

[0044] <Shape retention> Small pieces (soaked) of the resin compositions obtained in the Examples and Comparative Examples were heated to (melting point -10)°C when the polymer used was crystalline, and to (glass transition point +10)°C when the polymer used was amorphous (Comparative Example 7), and the presence or absence of deformation was confirmed. Specifically, the small pieces (soaked) were first held for 10 minutes at the above temperatures depending on the presence or absence of crystallinity, and then returned to room temperature (23°C) to obtain heat-treated small pieces. The obtained heat-treated small pieces were then visually observed to check for the occurrence of deformation. In addition, the end faces of the heat-treated small pieces were placed on a horizontal surface, and the distance between the opposing end faces and the horizontal surface was measured to check for the occurrence of curling. The results were evaluated according to the following criteria. The results are shown in Table 1. A: No deformation or curling occurred. B: Deformation and / or curling occurs.

[0045] <Temperature advantage of molding> When molding a resin composition containing a crystalline polymer, it is generally assumed that the molding is performed at (melting point + 20)°C. First, the melting point of the resin composition to be measured was measured according to the above. Molding was attempted by lowering the set temperature by 1°C from a temperature of (melting point + 20)°C, and the temperature advantage of molding was evaluated according to the following criteria depending on the temperature at which molding became impossible. The results are shown in Table 1. A lower heating temperature required during molding is advantageous in that the time required to heat and cool the molded object is shorter than in the case of a higher heating temperature, making it possible to shorten the molding cycle, which is the time required for one molding, and in that less energy is consumed. A: It can be molded even at temperatures below (melting point + 13)℃ (i.e., it can be molded at temperatures 7℃ lower than the general molding temperature). B: Molding is possible even at temperatures above (melting point +13)℃ and below (melting point +17)℃ (i.e., molding is possible at temperatures 3℃ to 7℃ lower than the general molding temperature). C: Molding is possible even at temperatures above (melting point +17)℃ and below (melting point +19)℃ (i.e., molding is possible at temperatures 1℃ to 3℃ lower than the general molding temperature). D: The molding temperature was unchanged, or molding was possible at a temperature less than 1°C lower than the general molding temperature.

[0046] <Production Example of Hydrogenated Polymer> <<Production Example 1>> In a glass reactor equipped with a stirrer, 0.028 g of phenylimidotungsten (VI) tetrachloride tetrahydrofuran as a ring-opening polymerization catalyst and 5 ml of toluene were placed and stirred. Next, 27 g of cyclohexane, 0.22 g (2.5 mol%) of 1-octene, and 0.022 g of diethylaluminum ethoxide as an organometallic reducing agent dissolved in 1 ml of n-hexane were added to another glass reactor equipped with a stirrer. Next, a toluene solution of phenylimidotungsten (VI) tetrachloride tetrahydrofuran and 7.5 g of norbornene as a cyclic olefin compound were added over 2 hours, and a polymerization reaction was carried out at 50°C for 2 hours. After the start of the polymerization reaction, the viscosity of the reaction mixture gradually increased. The reaction was carried out for 2 hours to obtain a polymerization reaction liquid. A large amount of acetone was poured into a part of the obtained polymerization reaction liquid to flocculate the precipitate, and the flocculated product was collected by filtration. The collected product was washed with methanol and then dried under reduced pressure at 40°C for 24 hours. The yield of the obtained ring-opening polymer was 7.4 g. The obtained ring-opening polymer was subjected to the above-mentioned procedure. 1 H-NMR measurements were carried out.

[0047] The polymerization reaction solution obtained above (without acetone added) was transferred to an autoclave equipped with a stirrer without precipitating 7.4 g equivalent to the mass of the ring-opening polymer, and 0.075 g of a diatomaceous earth supported nickel catalyst (T8400, nickel loading rate 58 mass%, manufactured by Nissan Süd-Chemie) was added as a heterogeneous catalyst as a hydrogenation catalyst, and the reaction was carried out at 200 ° C. and hydrogen pressure 4.5 MPa for 8 hours. This solution was filtered with a filter equipped with a stainless steel wire mesh using diatomaceous earth as a filter aid, and the resulting reaction solution was poured with a large amount of acetone to flocculate the precipitate, which was then filtered and washed, and dried under reduced pressure at 40 ° C. for 24 hours to obtain 7.5 g of a powdered ring-opening polymer hydrogenation product. The weight average molecular weight of the obtained ring-opening polymer hydrogenation product was 60,000. The ring-opening polymer hydrogenation product had a hydrogenation rate of 99.7% and a racemo-dyad ratio of 78%, which was syndiotactic. The isomerization rate of the hydrogenated ring-opening polymer was 3%. Furthermore, the melting point of the hydrogenated syndiotactic norbornene ring-opening polymer obtained in this example was observed to be 135° C. by DSC measurement, and it was found to be crystalline.

[0048] <<Production Example 2>> In a glass reactor equipped with a stirrer, 0.0463 g of bis{3,3'-di(t-butyl)-5,5',6,6'-tetramethyl-2,2'-biphenoxy}oxymolybdenum(VI) as a ring-opening polymerization catalyst and 4 ml of toluene were added, and the mixture was cooled to -78°C. 0.00726 g of n-butyllithium as an organometallic reducing agent dissolved in 1 ml of hexane was added thereto, and the temperature was returned to room temperature and reacted for 15 minutes. Next, 10.0 g of norbornene as a cyclic olefin compound, 27 g of cyclohexane, and 0.64 g of 1-hexene were added to the resulting reaction mixture, and a polymerization reaction was carried out at 50°C. After the start of the polymerization reaction, the viscosity of the mixture gradually increased. The reaction was carried out for 2 hours to obtain a polymerization reaction liquid. A large amount of acetone was poured into a part of the obtained polymerization reaction liquid to flocculate the precipitate, which was then filtered and washed, and dried under reduced pressure at 40°C for 24 hours. The yield of the obtained ring-opening polymer was 9.8 g. The obtained ring-opening polymer was subjected to the above-mentioned procedure. 1 H-NMR measurements were carried out.

[0049] 7.4 g of the ring-opened polymer of the polymerization reaction solution obtained above (without acetone added) was transferred to an autoclave equipped with a stirrer without precipitating, and 0.225 g of a diatomaceous earth supported nickel catalyst (T8400, nickel loading rate 58 mass%, Nissan Süd-Chemie) was added thereto, and the reaction was carried out for 8 hours at 200 °C and hydrogen pressure 4.5 MPa. This solution was filtered through a filter equipped with a stainless steel wire mesh using diatomaceous earth as a filter aid, and the resulting reaction solution was poured with a large amount of acetone to coagulate the precipitate, which was filtered and washed, and then dried under reduced pressure at 40 °C for 24 hours to obtain 7.5 g of a powdered ring-opened polymer hydrogenation product. The weight average molecular weight of the obtained ring-opened polymer hydrogenation product was 121,000. The ring-opened polymer hydrogenation product had a hydrogenation rate of 99.8%, and the ratio of racemo-dyads was 0% (i.e., the ratio of meso-dyads was 100%), and was isotactic. The isomerization rate of the hydrogenated ring-opening polymer was 10%. Furthermore, the melting point of the hydrogenated isotactic norbornene ring-opening polymer obtained in this example was observed to be 175° C. by DSC measurement, and it was found to be crystalline.

[0050] <<Production Example 3>> In a glass reactor equipped with a stirrer, 0.028 g of phenylimidotungsten (VI) tetrachloride tetrahydrofuran as a ring-opening polymerization catalyst and 5 ml of toluene were placed and stirred. Next, 27 g of cyclohexane, 0.22 g (2.5 mol%) of 1-octene, and 0.022 g of diethylaluminum ethoxide as an organometallic reducing agent dissolved in 1 ml of n-hexane were added to another glass reactor equipped with a stirrer. Next, a toluene solution of phenylimidotungsten (VI) tetrachloride tetrahydrofuran and 7.5 g of dicyclopentadiene as a cyclic olefin compound were added over 2 hours, and a polymerization reaction was carried out at 50°C for 2 hours. After the polymerization reaction started, the viscosity of the reaction mixture gradually increased. After the reaction for 2 hours, a large amount of acetone was poured into the polymerization reaction liquid to flocculate the precipitate, and the flocculated product was collected by filtration. The product was washed with methanol and then dried under reduced pressure at 40°C for 24 hours. The yield of the obtained ring-opening polymer was 7.4 g. The obtained ring-opening polymer was subjected to the above-mentioned procedure. 1 H-NMR measurements were carried out.

[0051] 5 g of the obtained ring-opening polymer, 100 g of paratoluenesulfonylhydrazide as a hydrogenating agent, and 200 g of paraxylene were added to a glass reactor equipped with a stirrer, and hydrogenation was performed by heating at 125 ° C for 5 hours. The obtained reaction solution was poured into a large amount of methanol to flocculate the precipitate, and after filtration and washing, it was dried under reduced pressure at 40 ° C for 24 hours to obtain 5.0 g of ring-opening polymer hydrogenated powder. The weight average molecular weight of the obtained ring-opening polymer hydrogenated product was 50,000. The ring-opening polymer hydrogenated product had a hydrogenation rate of 99.8% and a racemo-dyad ratio of 90%, and was syndiotactic. The isomerization rate of the ring-opening polymer hydrogenated product was 0%. Furthermore, the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product obtained in this example was observed to have a melting point of 270 ° C by DSC measurement, and was found to be crystalline.

[0052] <<Production Example 4>> In a glass reactor equipped with a stirrer, 0.0463 g of bis{3,3'-di(t-butyl)-5,5',6,6'-tetramethyl-2,2'-biphenoxy}oxymolybdenum(VI) as a ring-opening polymerization catalyst and 4 ml of toluene were added, and the mixture was cooled to -78°C. 0.00726 g of n-butyllithium as an organometallic reducing agent dissolved in 1 ml of hexane was added thereto, and the temperature was returned to room temperature and reacted for 15 minutes. Next, 10.0 g of dicyclopentadiene as a cyclic olefin compound, 27 g of cyclohexane, and 0.64 g of 1-hexene were added to the resulting reaction mixture, and a polymerization reaction was carried out at 50°C. After the polymerization reaction started, the viscosity of the mixture gradually increased. After reacting for 2 hours, a large amount of acetone was poured into the polymerization reaction liquid to flocculate the precipitate, which was then filtered, washed, and dried under reduced pressure at 40°C for 24 hours. The yield of the resulting ring-opening polymer was 9.8 g.

[0053] 5 g of the obtained ring-opened polymer, 100 g of paratoluenesulfonylhydrazide, and 200 g of paraxylene were added to a glass reactor equipped with a stirrer, and the mixture was heated at 125°C for 5 hours to perform hydrogenation. The obtained reaction solution was poured into a large amount of methanol to flocculate the precipitate, which was then filtered and washed, and dried under reduced pressure at 40°C for 24 hours to obtain 5.0 g of a powdered ring-opened polymer hydrogenation product. The weight-average molecular weight of the obtained ring-opened polymer hydrogenation product was 85,000. The ring-opened polymer hydrogenation product had a hydrogenation rate of 99.8% and a rate of racemo-dyads of 0% (i.e., a rate of meso-dyads of 100%), and was isotactic. The isomerization rate of the ring-opened polymer hydrogenation product was 0%. Furthermore, the melting point of the isotactic dicyclopentadiene ring-opened polymer hydrogenation product obtained in this example was observed to be 285°C by DSC measurement, and it was found to be crystalline.

[0054] <<Production Example 5>> In a glass reactor equipped with a stirrer, 0.0745 g of tetrakis(2,6-dimethylphenoxy)oxymolybdenum(VI) as a ring-opening polymerization catalyst and 4 ml of toluene were added, and the mixture was cooled to -78°C. 0.0160 g of n-butyllithium as an organometallic reducing agent dissolved in 1 ml of hexane was added thereto, and the temperature was returned to room temperature and reacted for 15 minutes. Next, 10.0 g of tetracyclododecene as a cyclic olefin compound, 27 g of cyclohexane, and 0.64 g of 1-hexene were added to the resulting reaction mixture, and polymerization reaction was carried out at 50°C. After the start of the polymerization reaction, the viscosity of the mixture gradually increased. After reacting for 2 hours, a large amount of acetone was poured into the polymerization reaction liquid to flocculate the precipitate, which was then filtered, washed, and dried under reduced pressure at 40°C for 24 hours. The yield of the resulting ring-opening polymer was 9.8 g. The resulting ring-opening polymer was subjected to the above-mentioned procedure. 1 H-NMR measurements were carried out.

[0055] 5 g of the obtained ring-opening polymer, 100 g of paratoluenesulfonylhydrazide as a hydrogenating agent, and 200 g of paraxylene were added to a glass reactor equipped with a stirrer, and hydrogenation was performed by heating at 125 ° C for 5 hours. The obtained reaction solution was poured into a large amount of methanol to flocculate the precipitate, and after filtration and washing, it was dried under reduced pressure at 40 ° C for 24 hours to obtain 5.0 g of ring-opening polymer hydrogenated powder. The weight average molecular weight of the obtained ring-opening polymer hydrogenated product was 40,000. The ring-opening polymer hydrogenated product had a hydrogenation rate of 99.8% and a racemo-dyad ratio of 30%, and was isotactic. The isomerization rate of the ring-opening polymer hydrogenated product was 0%. Furthermore, the melting point of the isotactic tetracyclododecene ring-opening polymer hydrogenated product obtained in this example was observed to be 310 ° C by DSC measurement, and it was found to be crystalline.

[0056] Example 1 The hydrogenated syndiotactic norbornene ring-opening polymer obtained in Production Example 1 was melt-compressed and molded in a vacuum hot press heated to 200°C to obtain a small piece of 2 mm x 2 mm x 1 mm (hydrogenated syndiotactic norbornene ring-opening polymer a). The density of the small piece (g / cm 3) was 1.01. The organic solvent content of the small pieces (hydrogenated ring-opened polymer a) was measured according to the above and found to be 0%. The obtained small pieces were immersed in toluene as an organic solvent for 2 hours under normal pressure and room temperature (23°C) conditions, but did not dissolve at all and did not lose their shape. After removing the small pieces from the toluene, the toluene on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at room temperature (23°C) under reduced pressure, and although no visible change in shape was observed, a mass increase of 8% by mass was observed relative to 100% by mass of norbornene ring-opened polymer hydrogenation. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 8% by mass (based on the amount of hydrogenated ring-opened polymer), which was equal to the value of the mass increase. That is, as a result of the above series of operations, a resin composition A was obtained, which is a toluene-containing syndiotactic crystalline norbornene ring-opening polymer hydrogenated product, containing 8 mass% of toluene as an organic solvent relative to 100 mass% of the syndiotactic norbornene ring-opening polymer hydrogenated product a. The density (g / cm 3 ) was 1.05.

[0057] Example 2 The hydrogenated isotactic norbornene ring-opening polymer obtained in Production Example 2 was melt-compressed and molded in a vacuum hot press heated to 200°C to obtain a small piece of 2 mm x 2 mm x 1 mm (hydrogenated isotactic norbornene ring-opening polymer b). The density (g / cm 3) was 1.01. The organic solvent content of the small pieces (ring-opened polymer hydrogenated product b) was measured according to the above and found to be 0%. The obtained small pieces were immersed in chloroform as an organic solvent for 5 hours under normal pressure and room temperature (23°C) conditions, but did not dissolve at all and did not lose their shape. After removing the small pieces from the chloroform, the chloroform on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried at room temperature (23°C) under a reduced pressure atmosphere, and although no visible change in shape was observed, a mass increase of 9% by mass was observed. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 9% by mass (based on the amount of ring-opened polymer hydrogenated substance), which was equal to the mass increase. That is, a resin composition B was obtained, which is a chloroform-containing isotactic crystalline norbornene ring-opened polymer hydrogenated product, containing 9% by mass of chloroform as an organic solvent relative to 100% by mass of isotactic norbornene ring-opened polymer hydrogenated product b. Density of resin composition B (g / cm 3 ) was 1.07.

[0058] Example 3 The syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product obtained in Production Example 3 was melt-compressed and molded in a vacuum hot press machine heated to 300°C to obtain a small piece of 2 mm x 2 mm x 1 mm (syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product c). The density of the small piece (g / cm 3) was 1.01. The organic solvent content of the small pieces (ring-opening polymer hydrogenated product c) was measured according to the above and found to be 0%. The obtained small pieces were immersed in carbon disulfide as an organic solvent under normal pressure and room temperature (23°C) conditions for 3 hours, but did not dissolve at all and did not lose their shape. After removing the small pieces from the carbon disulfide, the carbon disulfide on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at room temperature (23°C) under reduced pressure, and although no change in shape was observed visually, a mass increase of 10% by mass was observed relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 10% by mass (based on the amount of ring-opening polymer hydrogenated product), which was equal to the value of the mass increase. That is, a resin composition C was obtained, which is a carbon disulfide-containing syndiotactic crystalline dicyclopentadiene ring-opening polymer hydrogenated product, containing 10% by mass of carbon disulfide relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The density of the resin composition C (g / cm 3 ) was 1.06.

[0059] Example 4 The hydrogenated isotactic dicyclopentadiene ring-opening polymer obtained in Production Example 4 was melt-compressed and molded in a vacuum hot press heated to 300°C to obtain a small piece of 2 mm x 2 mm x 1 mm (hydrogenated isotactic dicyclopentadiene ring-opening polymer d). The density of the small piece (g / cm 3) was 1.01. The organic solvent content of the small pieces (hydrogenated ring-opened polymer d) was measured according to the above and found to be 0%. The obtained small pieces were immersed in xylene as an organic solvent for 5 hours under normal pressure and room temperature (23°C) conditions, but did not dissolve at all and did not lose their shape. After removing the small pieces from the xylene, the xylene on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at normal temperature (23°C) under reduced pressure, and although no change in shape was observed visually, a mass increase of 8% by mass was observed relative to 100% by mass of isotactic dicyclopentadiene ring-opened polymer hydrogenation was observed. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 8% by mass (based on the amount of hydrogenated ring-opened polymer), which was equal to the value of the mass increase. That is, a resin composition D was obtained, which is a xylene-containing isotactic crystalline dicyclopentadiene ring-opening polymer hydrogenated product, containing 8% by mass of xylene relative to 100% by mass of the isotactic dicyclopentadiene ring-opening polymer hydrogenated product. The density of the resin composition D (g / cm 3 ) was 1.04.

[0060] Example 5 The syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product obtained in Production Example 3 was melt-compressed and molded in a vacuum hot press machine heated to 300°C to obtain a small piece of 2 mm x 2 mm x 1 mm (syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product c). The density of the small piece (g / cm 3) was 1.00. The organic solvent content of the small pieces (ring-opening polymer hydrogenated product c) was measured according to the above and found to be 0%. The obtained small pieces were immersed in toluene as an organic solvent for 15 minutes under normal pressure and room temperature (23°C) conditions, but did not dissolve at all and did not lose their shape. After removing the small pieces from the toluene, the toluene on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at room temperature (23°C) under a reduced pressure atmosphere, and although no change in shape was observed visually, a mass increase of 1.5% by mass was observed relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 1.5% by mass (based on the amount of ring-opening polymer hydrogenated product), which was equal to the value of the mass increase. That is, a resin composition E was obtained, which was a toluene-containing syndiotactic crystalline dicyclopentadiene ring-opening polymer hydrogenated product, containing 1.5 mass% toluene relative to 100 mass% of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The density of the resin composition E (g / cm 3 ) was 1.02.

[0061] Example 6 The syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product obtained in Production Example 3 was melt-compressed and molded in a vacuum hot press machine heated to 300°C to obtain a small piece of 2 mm x 2 mm x 1 mm (syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product c). The density of the small piece (g / cm 3) was 1.01. The organic solvent content of the small pieces (ring-opening polymer hydrogenated product c) was measured according to the above and found to be 0%. The obtained small pieces were immersed in cyclohexane as an organic solvent under normal pressure and room temperature (23°C) conditions for 24 hours, but did not dissolve at all and did not lose their shape. After removing the small pieces from the cyclohexane, the cyclohexane on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at room temperature (23°C) under a reduced pressure atmosphere, and although no change in shape was observed visually, a 3% mass increase was observed relative to 100% mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 3% mass (based on the amount of ring-opening polymer hydrogenated product), which was equal to the mass increase. That is, resin composition F was obtained, which is a cyclohexane-containing syndiotactic crystalline dicyclopentadiene ring-opening polymer hydrogenated product, containing 3% by mass of cyclohexane relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The density of resin composition F (g / cm 3 ) was 1.02.

[0062] Example 7 The hydrogenated syndiotactic dicyclopentadiene ring-opening polymer obtained in Production Example 3 was melt-compressed and molded in a vacuum hot press heated to 300°C to obtain a small piece of 2 mm x 2 mm x 1 mm (hydrogenated syndiotactic dicyclopentadiene ring-opening polymer c). The density of the small piece (g / cm 3) was 1.01. The organic solvent content of the small pieces (ring-opening polymer hydrogenated product c) was measured according to the above and found to be 0%. The obtained small pieces were immersed in chloroform as an organic solvent under normal pressure and room temperature (23°C) conditions for 5 hours, but did not dissolve at all and did not lose their shape. After removing the small pieces from the chloroform, the chloroform on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at normal temperature (23°C) under reduced pressure, and although no change in shape was observed visually, a mass increase of 6% by mass was observed relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 6% by mass (based on the amount of ring-opening polymer hydrogenated product), which was equal to the value of the mass increase. That is, a resin composition G was obtained, which was a chloroform-containing syndiotactic crystalline dicyclopentadiene ring-opening polymer hydrogenated product, containing 6% by mass of chloroform relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opening polymer hydrogenated product. The density of the resin composition G (g / cm 3 ) was 1.03.

[0063] Example 8 The hydrogenated isotactic tetracyclododecene ring-opening polymer obtained in Production Example 5 was melt-compressed and molded in a vacuum hot press heated to 330°C to obtain a small piece of 2 mm x 2 mm x 1 mm (hydrogenated isotactic tetracyclododecene ring-opening polymer h). The density of the small piece (g / cm 3) was 1.01. The organic solvent content of the small pieces (hydrogenated ring-opened polymer h) was measured according to the above and found to be 0%. The obtained small pieces were immersed in toluene as an organic solvent for 5 hours under normal pressure and room temperature (23°C) conditions, but did not dissolve at all and did not lose their shape. After removing the small pieces from the toluene, the toluene on the surface was wiped off with dry gauze. Furthermore, the small pieces were dried for 10 minutes at room temperature (23°C) under reduced pressure, and although no change in shape was observed visually, a weight increase of 7% by mass was observed relative to 100% by mass of the syndiotactic dicyclopentadiene ring-opened polymer hydrogenated product. The organic solvent content of the small pieces that had undergone a series of operations was measured according to the above and found to be 7% by mass (based on the amount of hydrogenated ring-opened polymer), which was equal to the value of the mass increase. That is, a resin composition H was obtained, which is a toluene-containing hydrogenated isotactic tetracyclododecene ring-opening polymer, containing 7% by mass of toluene relative to 100% by mass of the hydrogenated isotactic tetracyclododecene ring-opening polymer. The density (g / cm 3 ) was 1.04.

[0064] (Comparative Examples 1 to 5) The small pieces prepared in Examples 1 to 4 and Example 8, that is, the ring-opening polymer hydrogenated products a to d and h, were used as shown in Table 1. The small pieces were evaluated for shape retention and molding temperature advantage according to the above without immersion in an organic solvent and drying following the immersion. The results are shown in Table 1.

[0065] Comparative Example 6 The hydrogenated syndiotactic dicyclopentadiene ring-opening polymer obtained in Production Example 3 was molded into a film having a thickness of 150 μm and a width of 120 mm using a hot melt extrusion film molding machine equipped with a T-die, and wound into a roll at a speed of 2 m / min. The operating conditions of the film molding machine are shown below. Barrel temperature setting: 280~290℃ Die temperature: 270℃ Screw speed: 30 rpm A part of the obtained resin film was cut into a size of 90 mm × 90 mm, and then placed in a small stretching machine (TOYO SEIKI SEISAKUSHO: EX10-B type) and stretched to obtain a stretched film 1. The operating conditions of the small stretching machine are shown below. ·Stretching speed: 10000mm / min ·Stretching temperature: 100℃ Stretching ratio: 1.8 times (machine direction of resin film (MD)) Density of stretched film 1 (g / cm 3 ) was 1.01. The organic solvent content of the stretched film 1 was measured according to the above and was found to be 0%. The obtained stretched film 1 was immersed in toluene at 23°C for 30 seconds, the surface was wiped with dry gauze, and then dried at room temperature (23°C) under reduced pressure for 10 minutes. Although no change in shape was observed by visual inspection, the stretched film 1 showed only a 0.1% increase in mass relative to 100% by mass. The organic solvent content of the toluene-containing stretched film 1 was measured as described above, and was 0.1% by mass (based on the amount of hydrogenated ring-opening polymer), which was equal to the mass increase. The density (g / cm 3 ) was 1.01.

[0066] Comparative Example 7 In a glass reactor equipped with a stirrer, 0.006 g of (1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene)dichloro(phenylmethylene)(tricyclohexylphosphine)ruthenium as a ring-opening polymerization catalyst and 5 ml of toluene were placed and stirred. Next, 27 g of cyclohexane and 0.09 g (1.0 mol%) of 1-octene were added to another glass reactor equipped with a stirrer. Next, 7.5 g of dicyclopentadiene as a cyclic olefin compound was added over 2 hours, and a polymerization reaction was carried out at 50°C for 2 hours. After the start of the polymerization reaction, the viscosity of the reaction mixture gradually increased. After the reaction for 2 hours, a large amount of acetone was poured into the polymerization reaction liquid to flocculate the precipitate, and the flocculate was filtered. The filtered product was washed with methanol and then dried under reduced pressure at 40°C for 24 hours. The yield of the obtained ring-opened polymer was 7.4 g. The obtained ring-opened polymer was subjected to the above-mentioned procedure. 1 H-NMR measurements were carried out.

[0067] 5 g of the obtained ring-opening polymer, 100 g of paratoluenesulfonylhydrazide as a hydrogenating agent, and 200 g of paraxylene were added to a glass reactor equipped with a stirrer, and hydrogenation was performed by heating at 125 ° C for 5 hours. The obtained reaction solution was poured into a large amount of methanol to flocculate the precipitate, and after filtration and washing, it was dried under reduced pressure at 40 ° C for 24 hours to obtain 5.0 g of ring-opening polymer hydrogenated powder. The weight average molecular weight of the obtained ring-opening polymer hydrogenated product was 25,000. The ring-opening polymer hydrogenated product had a hydrogenation rate of 99.8% and a racemo-dyad ratio of 50%, and was atactic. The isomerization rate of the ring-opening polymer hydrogenated product was 0%. Furthermore, the atactic dicyclopentadiene ring-opening polymer hydrogenated product obtained in this example did not have a melting point observed by DSC measurement, and was found to be amorphous.

[0068] The obtained atactic dicyclopentadiene ring-opening polymer hydrogenated product was melt-compressed and molded in a vacuum hot press heated to 300°C to obtain a small piece of 2 mm x 2 mm x 1 mm (atactic dicyclopentadiene ring-opening polymer hydrogenated product i). The density (g / cm 3) was 1.00. The organic solvent content of the small piece (hydrogenated ring-opened polymer i) was measured according to the above and found to be 0%. The obtained small piece was immersed in xylene for 5 hours under normal pressure and room temperature (23°C) conditions, but it swelled from the surface toward the inside, became cloudy, and did not maintain its shape. After removing the small piece from the xylene, the xylene on the surface was wiped off with dry gauze and dried for 10 minutes at room temperature (23°C) under reduced pressure. A clear change in shape was observed with the naked eye, and a weight increase of about 80% by mass was observed relative to 100% by mass of the hydrogenated atactic dicyclopentadiene ring-opened polymer. That is, a xylene-containing hydrogenated atactic dicyclopentadiene ring-opened polymer I was obtained, which contained 80% by mass of xylene relative to 100% by mass of the hydrogenated atactic dicyclopentadiene ring-opened polymer i. Density (g / cm3) of hydrogenated atactic dicyclopentadiene ring-opening polymer containing xylene I 3 ) was 0.96. The xylene-containing atactic dicyclopentadiene ring-opening polymer hydrogenated product I obtained in this comparative example was amorphous and had no melting point, so the melting point was not measured.

[0069] In Table 1, "NB" stands for norbornene, "DCP" stands for dicyclopentadiene. "TCD" stands for tetracyclododecene. Each is shown.

[0070] [Table 1]

[0071] According to Examples 1 to 8, it is understood that it was possible to produce a resin composition that has high shape retention when a molded product is formed and requires a reduced heating temperature in the molding process. It is also understood that the resin compositions according to Comparative Examples 1 to 5, which do not contain an organic solvent, and the resin composition according to Comparative Example 6, which has a low content of an organic solvent, could not reduce the heating temperature during molding at all. Furthermore, it is understood that in the resin composition I according to Comparative Example 7, which is made of an amorphous polymer, the introduction of an organic solvent into the resin composition did not increase the density of the resin composition, but rather decreased the density, and it was not even possible to ensure good shape retention. [Industrial Applicability]

[0072] According to the present invention, it is possible to provide a resin composition that has high shape retention when a molded product is formed and requires a reduced heating temperature in the molding step, and a method for producing the same. Furthermore, according to the present invention, a molded product having high shape retention can be provided.

Claims

1. A crystalline polymer having a structural unit derived from a cyclic olefin compound; an organic solvent, the crystalline polymer is a ring-opening polymer hydrogenate, Density: 1.02 g / cm 3 That's all. A content of the organic solvent relative to 100% by mass of the polymer is 1.0% by mass or more and 10% by mass or less, The content of other components other than the crystalline polymer and the organic solvent is 30% by mass or less based on 100% by mass of the polymer. Resin composition.

2. The resin composition according to claim 1 , wherein the hydrogenation rate of the polymer is 90% or more.

3. The resin composition according to claim 1 or 2, wherein the organic solvent is a non-polar solvent.

4. A molded product obtained by molding the resin composition according to any one of claims 1 to 3.

5. A dipping step of dipping a polymer material made of a crystalline polymer having structural units derived from a cyclic olefin compound in an organic solvent; The polymer material that has been subjected to the immersion step is dried under an atmosphere of a pressure of 1000 Pa to 6000 Pa and a temperature of 5° C. to 35° C. to reduce the density to 1.02 g / cm 3 A drying step of obtaining a resin composition having the above-mentioned properties and a content of the organic solvent relative to 100% by mass of the polymer, the resin composition being 1.0% by mass or more and 10% by mass or less; Including, the crystalline polymer is a ring-opening polymer hydrogenate, In the resin composition, the content of other components other than the crystalline polymer and the organic solvent is 30% by mass or less with respect to 100% by mass of the polymer. A method for producing a resin composition.

Citation Information

Patent Citations

  • Method for producing resin film, resin film, and optical film

    JP2016026909A

  • Purification method of cyclic olefin polymer, and production method of cyclic olefin polymer

    JP2016183221A